2022
DOI: 10.33457/ijhsrp.1018314
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Professional Development (Cpd) of Doctors in Sri Lanka: A Qualitative Study.

Abstract: Continuous professional development is the method by which doctors maintain their knowledge, abilities, and attitudes up to date to meet the demands of their patients, the health service, and their career growth. The goal of this study is to evaluate Sri Lanka's present continuous professional development program for medical officers. This qualitative study was conducted from January 2020 to August 2020 at the Ministry of Health, Sri Lanka. Data was gathered through in-depth interviews, as well as two focus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A few research studies have delved into and analysed reasons for the lack of active participation in CPD activities by medical professionals in Sri Lanka. A qualitative study conducted in 2020 concluded that the major reasons for nonengagement in CPD activities were, an absence of a well-organized and streamlined programs for medical officers, lack of interest to such programs by Grade Medical Officers (GMOs), programs not reaching remote areas of the country and lack of financial incentives for CPD related activities (Sabhapathige et al, 2022). Another study, which made a SWOT matrix analysis of implementation of CPD for GMOs in Sri Lanka identified lack of financial incentives, lack of CPD infrastructure, remoteness of doctors from main educational centers, lack of time and CPD being noncompulsory by law for re-validation (Samarasinghe et al, 2020).…”
Section: Challenges In Implementing a National Cpd Frameworkmentioning
confidence: 99%
“…A few research studies have delved into and analysed reasons for the lack of active participation in CPD activities by medical professionals in Sri Lanka. A qualitative study conducted in 2020 concluded that the major reasons for nonengagement in CPD activities were, an absence of a well-organized and streamlined programs for medical officers, lack of interest to such programs by Grade Medical Officers (GMOs), programs not reaching remote areas of the country and lack of financial incentives for CPD related activities (Sabhapathige et al, 2022). Another study, which made a SWOT matrix analysis of implementation of CPD for GMOs in Sri Lanka identified lack of financial incentives, lack of CPD infrastructure, remoteness of doctors from main educational centers, lack of time and CPD being noncompulsory by law for re-validation (Samarasinghe et al, 2020).…”
Section: Challenges In Implementing a National Cpd Frameworkmentioning
confidence: 99%